Science Fiction Cinema and 1950s Britain Recontextualising the Golden Age - Jones, Matthew (Bloomsbury Academic, 2017)
For the last fifty years, discussion of 1950s science fiction cinema has been dominated by the view that the genre reflected US paranoia about Soviet brainwashing and the nuclear bomb. However, classic films, such as Invasion of the Body Snatchers (1956) and It Came from Outer Space (1953), were regularly exported to countries across the world. The histories of their encounters with foreign audiences have not yet been told. Science Fiction Cinema and 1950s Britain begins this task by recounting the story of 1950s British cinema-goers and the aliens and monsters they watched on the silver screen. Drawing on extensive archival research, Matthew Jones makes an exciting and important intervention in the field by locating 1950s American science fiction films alongside their domestic counterparts in their British contexts of release and reception.